“Desarrollo de alternativas orgánicas – biológicas para el manejo de nemátodos en bananeras orgánicas de las provincias de Guayas y Los Ríos - Sánchez Jaime, Luis Enrique (2011)
This work was carried out in two banana plantations cv Cavendish infested with the lesion nematode Radopholus similis and Helicotylenchus multicinctus. They were located in the San José farm in the Babahoyo canton, of Los Ríos province, and the other on Andreina farm in the Naranjal canton, province of Guayas. The objective was to determine organic and biological alternatives to reduce nematode populations in organic banana plantations in the mentioned provinces. There were 10 studied treatments: 1) leaching of noni fruit, 2) leaching of rachis + banana fingers, 3) leaching of rachis + manure + ME; 4) leaching of rachis + cocoa shells; 5) leaching of rachis dehydrated + manure + coffee shell + ash + humus + P. lilacinus Ec; 6) leaching of rachis + yogurt + yeast + molasses + P. lilacinus; 7) leaching of rachis + manure + ash + ME + T. harzianum; 8) Cytokin commercial product; 9) farmer maintenance and 10) absolute control. The design was a randomized complete block. Those leaching were applied at doses of 50 cc/plant, fungi 10 x 506 spore/plant and Cytokin 50 x 0.3 ml/plant. There were applied every 30 days during the first 6 months of work. Roots were sampled and evaluated even two month: total root weight by 13.5 dm3/plant, percentage of healthy roots, population density of R. similis and H. multicinctus in 100 g of roots. At the end of the plant cycle of the first generation there was evaluated for fruit yield. According to the results obtained in the San José farm, in most of the variables evaluated those treatments were not significantly different, however, it is very clear that the seven leaching treatments reduced populations of R. similis and H. multicinctus. The leached of rachis + manure + ash + ME, followed by a separate application of antagonistic fungus T. harzianum, influenced in the production of higher bunch weight, but did not increased the total root weight and the percentage of healthy roots. In Andreina farm, the noni fruit, leaching of rachis + banana fingers, leaching of rachis + yogurt + yeast + molasses, followed by a separate application of P. lilacinus antagonistic fungus (6), caused greater reduction in nematode populations density and higher bunch weight. In Los Ríos province, with the treatment, leaching of rachis + manure + ash + ME + T. harzianum (7) was obtained a yield of 2346 boxes/ha/year, and a return marginal rate of 99 %, while in the Guayas province with the leaching of rachis + yogurt + yeast + molasses + P. lilacinus (6) was obtained a yield of 1688 boxes/ha/year, and a return marginal rate of 467 %.